Treatment of breast cancer 2 (BRCA2)-mutant follicular dendritic cell sarcoma with a poly ADP-ribose polymerase (PARP) inhibitor: a case report. (December 2016) - Lemech, Charlotte; Williams, Rachel; Thompson, Stephen; McCaughan, Brian; Chin, Melvin
Abstract Background Follicular dendritic cell sarcoma is a rare tumour with clinical behaviour covering a spectrum from indolent to aggressive disease. Treatment recommendations are currently based on case reports and small series describing combinations of surgery, chemotherapy and radiotherapy providing the best patient outcomes. Recent knowledge on molecular aberrations in this disease have not yet impacted on therapeutic decisions. Case presentation We describe a case of progressive follicular dendritic cell sarcoma of the lung and pleura, treated based on knowledge of the tumour's molecular aberrations. The patient was initially treated with surgery, chemotherapy and radiotherapy and developed disease progression. Mutation testing by Caris molecular intelligence demonstrated a breast cancer 2 gene mutation and further treatment with carboplatin and veliparib achieved disease stabilisation. Conclusion Understanding of the molecular profile of rare tumours is key to improve therapeutic decision making and patient outcomes.